Pathological investigations on remil hemosiderosis in sheep - Hüdaverdi Erer; S. Serap Türkütanıt; Fatih Hatipoğlu (Eurasian Journal of Veterinary Sciences)
This study was undertaken to determine hemosiderosis in the kidneys of sheep slaughtered at abattoir. For this purpose, the kidneys of 3012 sheep were examined, and in 52 (1.72 %) was showed hemosiderosis. In terms of pigment concentrations, these cases were classified as ; mild, moderate and severe. There were hemosiderin pigments in distal and medullar tubular epithelium, with particular location in proximal tubulus.